Effect of Drought on Antioxidant System at Seedling and Vegetative Stage of Eleusine coracana - Sharma, Shipra; Arora, Sandeep; Lohani, Pushpa (International Journal of Applied Sciences and Biotechnology, 2015)
Adverse environmental factors like drought stress result in increased levels of ROS that adversely affect the growth and productivity of plants. The alleviation of oxidative damage and increased resistance to environmental stresses is correlated with an efficient antioxidant system. Antioxidant non enzymatic system as well as enzymatic system neutralize the effects of these reactive oxygen species and help plants to survive in stress conditions. The study was carried out with the aim to understand the effect of drought on antioxidant system in seedling and vegetative stages of drought tolerant as well as sensitive genotypes of Eleusine coracana. Drought was imposed by withholding water for 8 days at seedling and vegetative stages of drought tolerant ie PRM-6107 and sensitive ie PES-400 genotypes of E. coracana. Different enzyme assays and biochemical analysis were performed in leaf samples by following the standard protocols. With the induction of drought, an increment in the level of ascorbate, flavonoid, phenol and proline was recorded in PRM-6107 whereas no significant increase was observed in PES-400. The level of these antioxidants was more in seedling stage than at vegetative stage. Similarly the level of antioxidant enzymes like ascorbate peroxidase, catalase, guaicol peroxidase, superoxide dismutase and glutathione reductase was high in tolerant genotype as compared to sensitive genotype under unstressed condition. Under stress condition, the level of catalase, ascorbate peroxidase and guaicol peroxidase increased at seedling stage while the levels of glutathione reductase and superoxide dismutase increased significantly at vegetative stage of both the genotypes. These results show that PRM-6107 is drought tolerant because the level of antioxidants as well as antioxidative enzymes is high in this genotype in seedling and vegetative stages. Also, the elevated levels of antioxidants and antioxidative enzymes at seedling stage show that plant start combating drought more strongly at seedling stage than at vegetative stage. Int J Appl Sci Biotechnol, Vol 3(4): 642-650